Enlarging the knowledge on Didelphis albiventris (Didelphimorphia, Didelphidae) in northern Patagonia: new records and distribution extention - Carrera, Marcelo (2014)
Fil: Carrera, Marcelo. Universidad Nacional de la Patagonia San Juan Bosco. Sede Puerto Madryn; Argentina